2009
DOI: 10.1002/ar.20932
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Microarchitecture of Hominoid Thoracic Vertebrae

Abstract: Spontaneous vertebral fractures are a common occurrence in modern humans, yet these fractures are not documented in other hominoids. Differences in vertebral bone strength between humans and apes associated with trabecular bone microarchitecture may contribute to differences in fracture incidence. We used microcomputed tomography to examine trabecular bone microarchitecture in the T8 vertebra of extant young adult hominoids. Scaled volumes of interest from the anterior vertebral body were analyzed at a resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 43 publications
7
77
0
3
Order By: Relevance
“…4). Although these data are consistent with other findings that apes tend to have thicker cortical bone than humans (Cotter et al, 2009), they are unexpected if tensile forces produced by the Achilles were influencing cortical thickness. Along these same lines, we do find one aspect of our negative results as potentially illuminating and worthy of further consideration.…”
Section: Discussionsupporting
confidence: 92%
“…4). Although these data are consistent with other findings that apes tend to have thicker cortical bone than humans (Cotter et al, 2009), they are unexpected if tensile forces produced by the Achilles were influencing cortical thickness. Along these same lines, we do find one aspect of our negative results as potentially illuminating and worthy of further consideration.…”
Section: Discussionsupporting
confidence: 92%
“…To begin with, the body size range of the sample appears to impact the scaling relationship of Tb.Th when the results reported here are compared with those for hominoids and mammals. Femoral, humeral, and vertebral trabecular thicknesses consistently scale with negative allometry in broad samplings of nonvolant mammals and in hominoids (Swartz et al, 1998;Cotter et al, 2009;Doube et al, 2011). But in those studies the specimen samples included species with body masses much greater than the strepsirhine species sampled here.…”
Section: Strepsirhine Vertebral Body Microstructural Scalingmentioning
confidence: 79%
“…At present, reconciling these strepsirhine lumbar vertebral body data with other comparative and scaling studies is challenging. Studies vary in trabecular morphometric approaches (three-dimensional direct transformation, two-dimensional plate model, and twodimensional direct measures), taxonomic samples, target bones, the size variable used to determine allometric equations (femoral head radius, estimated body mass from skeletal dimensions, and published species body mass averages) and scaling results (Mullender et al, 1996;Swartz et al, 1998;Fajardo and Mü ller, 2001;MacLatchy and Mü ller, 2002;Ryan and Ketcham, 2002;Fajardo et al, 2007b;Cotter et al, 2009;Ryan and Walker, 2010;Doube et al, 2011). The few studies that have investigated comparative strepsirhine trabecular bone architecture have not assessed the scaling relationships quantitatively.…”
Section: Strepsirhine Vertebral Body Microstructural Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of this relative gracility remains uncertain, and this uncertainty hinders the development of strategies for mitigating fracture risk and morbidity. The progressive gracilization of the Homo postcranial skeleton was originally detected in cortical bone structure (1, 2), but has now been demonstrated in the trabecular bone microstructure of joints (12,14,(16)(17)(18)(19), where osteoporotic fracture risk is highest (20). Most notably, in an analysis of thoracic vertebral bodies, Cotter et al (12) found that young adult humans have significantly lower trabecular bone volume fraction (BV/TV) and thinner vertebral shells than similarly sized apes.…”
mentioning
confidence: 99%